Shifting diets: Toward a sustainable food future - Ranganathan, Janet; Vennard, Daniel; Waite, Richard; Searchinger, Tim; Dumas, Patrice; Lipinski, Brian (International Food Policy Research Institute, 2016)
A global convergence toward Western-style diets that are high in calories, protein, and animal-based foods poses challenges for food security and sustainability. To quantify the benefits of shifting these consumers to more sustainable diets, several possible diet shifts are modeled. A framework is proposed to tackle the crucial question of how to shift people’s diets through the retail and food services sector.